Comparative study of the effect antibiotics and feed ingredient containing probiotic bacteria from "Tchoukoutou" ferment on the immune status of local and exotic guinea fowl - GLAGO, Jean; TCHEKESSI, C. K. Célestin; KPOMASSE, C. Claude; CHABI, Worou Nicodème; TETE-BENISSAN, Amivi Kafu; HOUNDONOUGBO, Makpondji Frédéric; TONA, Jacob Kokou; CHRYSOSTOME, A. A. M.Christophe (My University, 2022)
Antibiotic resistance is a real public health problem related to the use of antibiotics in the production of animals feed. The present study aims to compare the effect of feed ingredient containing probiotic bacteria from “Tchoukoutou” ferment and antibiotics (alfaceryl) on the immune status of local and exotic guinea fowl (Numida meleagris). The birds of each strain were divided into three experimental treatments: treatment R1 received a feed ration containing 3% of this experimental ingredient while treatments R2 and R3 were fed a standard feed with R3 receiving alfaceryl. At the sixth week, blood samples were taken from 75 guinea fowl of each strain for the study of biochemical and hematological parameters. Regardless of the strain, there were notable the significant differences (p<0.05) in the values of total protein, red and white blood cells, hemoglobin, hematocrit, mean corpuscular volume and mean corpuscular hemoglobin concentration. This proved that the experimental ingredient improved health performance in these birds and the low proportions or even the absence of polynuclear cells revealed by the blood count showed that these animals were free from all infections. Conclusion: The ingredient has the same effect as alfaceryl on the immune status of these guinea fowl strains.
Keywords: probiotics; antibiotics; guinea fowl; biochemical and hematological parameters.